2019
DOI: 10.1142/s0218495819500171
|View full text |Cite
|
Sign up to set email alerts
|

Developing Cognitive and Non-Cognitive Entrepreneurial Competences through Business Simulation Games

Abstract: Today, entrepreneurship is seen as a major driver for innovation, economic growth and job creation, with entrepreneurial competencies highly sought after by practitioners and policy-makers alike. Competencies considered entrepreneurial include knowledge about how entrepreneurs create value; skills in marketing, resource acquisition and opportunity identification; and attitudes such as entrepreneurial passion, self-efficacy, proactiveness and tenacity. There is widespread consensus in the literature that entrep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 48 publications
0
35
0
4
Order By: Relevance
“… Costin et al (2019) studied the influence of simulation games in the development of cognitive (knowledge and skills) and non-cognitive (attitude) entrepreneurial capabilities using the existing entrepreneurial capability framework. The benefits of using business simulation as an effective model for developing entrepreneurial capabilities were demonstrated.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“… Costin et al (2019) studied the influence of simulation games in the development of cognitive (knowledge and skills) and non-cognitive (attitude) entrepreneurial capabilities using the existing entrepreneurial capability framework. The benefits of using business simulation as an effective model for developing entrepreneurial capabilities were demonstrated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is hoped that this study can reveal the relationship between entrepreneurial passion, selfefficacy, and psychology and behavior of entrepreneur, and expand the application of entrepreneurial passion in the field of entrepreneurship. Costin et al (2019) studied the influence of simulation games in the development of cognitive (knowledge and skills) and non-cognitive (attitude) entrepreneurial capabilities using the existing entrepreneurial capability framework. The benefits of using business simulation as an effective model for developing entrepreneurial capabilities were demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that higher education teachers and institutions should adopt interactive resources such as video games as, from the perspective of students, they benefit the learning process by fostering innovation skills and according to several authors (Raybourn, 2014;Ahrens, 2015;Liberona and Rojas, 2017;Costin et al, 2019), video games offer a good alternate to learn and motivate students, in such a way that learning can be given at any time and place and contribute to the strengthening of entrepreneurial skills as well.…”
Section: Itse 181mentioning
confidence: 91%
“…However, empirical evidence on its effects is limited. Some studies found that the use of SGs improves the teaching and development of entrepreneurial skills (Liberona and Rojas, 2017;Costin et al, 2019) and others bring to discuss these effects and their viability in EE (Charrouf and Taha Janan, 2019).…”
Section: Innovation Skills Using a Video Gamementioning
confidence: 99%